Land suitability zoning for ecotourism planning and development of Dikgatlhong Dam, Botswana - Šiljeg Ante; Cavrić Branko; Šiljeg Silvija; Marić Ivan; Barada Mirko (Geographica Pannonica, 2019)
The main objective of this paper was to discuss applications of GIS based multi-criteria decision analysis (GIS MCDA) and Analytical Hierarchy Process (AHP). These two techniques were applied in order to assist preparation of the Tourism Management Plan, depicting the most suitable zones for ecotourism development in Dikgathlong Dam Lease Area (DDLA) as one of the largest resources of potable water in Botswana. The MCDA was based on geo-morphometric, hydrologic, landscape and community indicators and criteria which emanated from expert's opinions, intensive field survey and literature review. In addition the AHP has helped to calculate individual criteria weights and to point the degree of suitability zones classified as highly suitable, moderately suitable, marginally suitable and not suitable for ecotourism. After performing both processes and establishing broad management zones it has been found that the Sustainable Development Scenario is the most appropriate option as the future ecotourism development proposal. This research provides new methodology that can be incorporated into future tourism policies and management strategies.